PENGARUH BUAH TERONG BELANDA (Solanum betaceum Cav.) TERHADAP JUMLAH ERITROSIT DAN KADAR HEMOGLOBIN MENCIT JANTAN (Mus musculus L.) ANEMIA STRAIN DDW MELALUI INDUKSI NATRIUM NITRIT (NaNO2) - Sister Sianturi; Masitta Tanjung; Emita Sabri (Saintia Biologi, 2013)
The effect  of  terong belanda (Solanum betaceum Cav.) juice on anemia mice DDW strain induced by sodium nitrite has been studied from March 2012 to August 2012 in the Laboratory of Animal Physiology and Laboratory of Tissue Culture, Department of Biology, Faculty of Mathematics and Natural Science, University of Sumatera Utara, Medan. This research performed with completely randomized design and was divided in two controls and three treatments. The treatments were divided into three classes concentration of juice such as: 40% (P1), 50% (P2), and 60% (P3) respectively. Each class consisted of six animals. The juice was given orally 0.3ml/day. Results indicated that juice of terong belanda in anemia male mice showed no significantly increased  in the number of erythrocytes if compared to either the anemia control or blank control, but significantly increased  in haemoglobin levels if compared to anemia control.   Keywords : erythrocytes, haemoglobin, Mus musculus, sodium nitrit, terong belanda